2021
DOI: 10.1186/s12877-021-02523-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver perspectives on a tool to increase recognition of undiagnosed dementia: a qualitative study

Abstract: Background Early detection of dementia may improve patient care and quality of life, yet up to half of people with dementia are undiagnosed. Electronic health record (EHR) data could be used to help identify individuals at risk of having undiagnosed dementia for outreach and assessment, but acceptability to people with dementia and caregivers is unknown. Methods We conducted five focus groups at Kaiser Permanente Washington (KPWA), an integrated he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This finding is similar to what has been reported in prior qualitative work evaluating undiagnosed cognitive impairment and dementia in the general population and those with medical comorbidities. Palazzo et al ( 30 ) found that older adults generally support an early diagnosis of cognitive impairment, describing benefits including time to adjust and plan for the future, involve caregivers or family in their care, and identify resources. In their qualitative work, participants emphasized the importance of thoughtful communication by a trusted provider and that a conversation about undiagnosed cognitive impairment should include advice about prognosis, treatment, and resources if cognitive impairment or dementia was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to what has been reported in prior qualitative work evaluating undiagnosed cognitive impairment and dementia in the general population and those with medical comorbidities. Palazzo et al ( 30 ) found that older adults generally support an early diagnosis of cognitive impairment, describing benefits including time to adjust and plan for the future, involve caregivers or family in their care, and identify resources. In their qualitative work, participants emphasized the importance of thoughtful communication by a trusted provider and that a conversation about undiagnosed cognitive impairment should include advice about prognosis, treatment, and resources if cognitive impairment or dementia was diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…Application of algorithms in electronic health records may potentially identify cognitive decline earlier for those at risk and in need of longitudinal assessment, 28 and such an approach may be acceptable to many patients and caregivers. 29 The second node in the healthcare system patient flow category is timely and accurate diagnosis. The theme for this node is improved timeliness and accuracy of AD diagnosis, and the example metric concept is the proportion of diagnoses made in early AD with appropriate biomarker components.…”
Section: Healthcare System Patient Flowmentioning
confidence: 99%
“…The ability to detect cognitive decline at earlier stages may necessitate changes to incorporate regular use of brief cognitive assessments by primary care personnel (physicians, nurse practitioners), in other settings (pharmacy, ophthalmology), and/or through community outreach programs. Application of algorithms in electronic health records may potentially identify cognitive decline earlier for those at risk and in need of longitudinal assessment, 28 and such an approach may be acceptable to many patients and caregivers 29 …”
Section: Ad System Preparedness Frameworkmentioning
confidence: 99%
“…Underdiagnosis of dementia is common across groups 4,5 though certain minoritized populations are more likely to experience missed and/or delayed dementia diagnoses 6–9 . A dementia diagnosis may benefit care partners, as it facilitates a better understanding of the PLWD, more timely identification of reversible conditions, earlier consideration of medications and nonpharmacological interventions, validation of patient/family concerns, and planning current and future care 10–13 …”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] A dementia diagnosis may benefit care partners, as it facilitates a better understanding of the PLWD, more timely identification of reversible conditions, earlier consideration of medications and nonpharmacological interventions, validation of patient/family concerns, and planning current and future care. [10][11][12][13] Given underdiagnosis and the growing diversity of PLWD, research into barriers and facilitators of dementia diagnoses in minoritized populations is urgent. Prior research found that minoritized groups face individual, provider, and systemic barriers to receiving diagnosis and care for many reasons, including normalization of memory loss as part of aging, stigma surrounding mental illness, clinical visit time constraints, distrust of healthcare providers, and racism/discrimination.…”
Section: Introductionmentioning
confidence: 99%